1992
DOI: 10.5014/ajot.46.7.626
|View full text |Cite
|
Sign up to set email alerts
|

Why Students Choose Occupational Therapy as a Career

Abstract: To recruit students to occupational therapy, we need to know what prospective students seek in careers. A survey consisting of an attitude inventory was sent to 403 current occupational therapy students with a response rate of 54%. Earlier research identified that students had primarily altruistic goals in selecting occupational therapy as a profession, and this study continued to find that students wanted to help others; however, this was not a predictor of their favoring the profession. A factor analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 9 publications
6
40
0
1
Order By: Relevance
“…Personal experience in the field influenced career choice and careers advisors had little impact. 8 The findings of recent studies on radiography and radiation therapy students are similar to earlier studies as there are many shared factors affecting career choice. These include the opportunity to help people, employment opportunities and technology.…”
Section: Literature Reviewsupporting
confidence: 74%
See 3 more Smart Citations
“…Personal experience in the field influenced career choice and careers advisors had little impact. 8 The findings of recent studies on radiography and radiation therapy students are similar to earlier studies as there are many shared factors affecting career choice. These include the opportunity to help people, employment opportunities and technology.…”
Section: Literature Reviewsupporting
confidence: 74%
“…Studies by Stewart, Pool and Winn (2002) and Rozier, Gilkeson and Hamilton (1992) on occupational therapy and physiotherapy students indicated that most students chose the career with the goal of helping others. 5,8 In addition, a study by Vosper, Price and Ashmore (2005) of radiography students found that the desire to help people was a highly motivating factor in career decisions. 2 Adams and Vann (2002) showed that female radiation therapy students chose the career to help patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive experiences were linked to retention in this study, while negative experiences were linked to attrition, echoing aspiring therapists' traditional desire to 'help people' (Rozier et al, 1992). The potential reasons for these findings vary.…”
Section: Discussionmentioning
confidence: 56%